Transcriptomic responses of selected genes against chromium stress in Arundo donax L. Issue 5 (3rd July 2017) - Shaheen, Shahida; Ahmad, Rafiq; Jin, Wang; Mahmood, Qaisar; Iqbal, Akhtar; Pervez, Arshid; Shah, Mohammad Maroof
ABSTRACT: Recently, giant reed (Arundo donax L.) has emerged as a useful bioresource capable of coping under harsh abiotic stress conditions produced by exposure to heavy metals, drought and salinity as evidenced by significant biomass production. The current study was undertaken to determine the expression of critical genes involved in resisting oxidative stress and maintaining normal cellular functions. The critical genes examined included glutathione reductase (GR) that prevents oxidative damage of membranes, carotenoid hydroxylase (CR), transcription factor (bHLH) and amidase involved in biosynthesis of indole-3-acetic acid following exposure to chromium (Cr) stress at concentrations of 0, 33.5, 67, 133 or 268 mg/L in giant reed. The S19 gene was used as internal control. It was not possible to extract RNA from severely stressed giant plant leaves at 133 and 268 mg/L Cr. Therefore, this investigation focused on gene expression in the presence of at 0, 33.5 or 67 mg/L Cr. Following Cr-mediated stress, gene expression of GR and CR was increased at 33.5 mg/L but reduced at 67 mg/L. The transcription factor, bHLH, gene expression remained unchanged. Amidase gene expression was elevated at 67 mg/L Cr. Data suggested that over expression of amidase and GR genes at high Cr exposure might increase growth and biomass of giant reed as well as enhance tolerance. These results indicated that giant reed tolerated the presence of Cr stress due to over expression of amidase and GR genes. It would appear that giant reed may serve a beneficial role for phytoremediation of Cr contaminated wastewater and soils at concentrations below 100 mg/kg.